Implementasi Model Pembelajaran Inquiry Terbimbing Melalui Pendekatan Berdiferensiasi Berbantuan Media Pembelajaran Kontekstual Untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas IV Sekolah Dasar - Oktianingsih Ari Rusmianto; Dyah Triwahyuningtyas; Aris Sri Sunarti (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to improve science learning result on plant material, the source of life on Earth by implementing a guided inquiry learning model through a differentiated content approach and a learning environment assisted by contextual learning media. The subjects of this research were 27 students of 4th grade at SDN Tanjungrejo 4, Malang City. This research is collaborative classroom action research (PTK) which was carried out in 2 cycles, each cycle containing 2 meetings with the stages of planning, implementation, observation and reflection. Data collection techniques in this research are observation, tests and documentation. This research shows that students' science learning result have increased starting from the pre-cycle, cycle 1 and cycle 2. In the pre-cycle stage, they got a percentage score of 63%, in cycle 1, the 1st meeting got a percentage score of 71.07%, in cycle 1, the 2nd meeting got a score of 73.14%, while the score from cycle 2 to 1st meeting was 79.76% and cycle 2 to 2nd meetings achieved a score of 85%. Based on the results of this research, it can be concluded that the guided inquiry learning model, differentiated approach and contextual learning media can improve student learning outcomes and this research was stopped until cycle 2 because the percentage score of learning outcomes had reached the researcher's target expectations.